THE USE OF INNOVATIVE METHODS IN LITERATURE CLASSES, SELF-EDUCATION IS THE BASIS OF STUDENTS’ COGNITIVE ACTIVITY - Xodjimetova, D.D. (Innovative Development in Educational Activities, 2023)
This article examines the use of innovative methods in literature lessons with a focus on self-education as the foundation of students’ educational activity. By incorporating digital storytelling, literature-based projects, community engagement, and cross-curricular integration, educators can create dynamic and engaging learning experiences that promote deeper understanding and appreciation of literature. The article highlights the benefits of these innovative methods, such as enhanced student engagement, motivation, critical thinking skills, and the development of lifelong learning habits. It also emphasizes the importance of providing teachers with necessary training, resources, and support to successfully implement these methods. Ultimately, the integration of innovative methods in literature lessons fosters self-directed learning and prepares students for the complexities of the 21st century.